2002
DOI: 10.1063/1.1450041
|View full text |Cite
|
Sign up to set email alerts
|

Production of nitrogen acceptors in ZnO by thermal annealing

Abstract: Nitrogen acceptors are formed when undoped single crystals of zinc oxide (ZnO) grown by the chemical-vapor transport method are annealed in air or nitrogen atmosphere at temperatures between 600 and 900 °C. After an anneal, an induced near-edge absorption band causes the crystals to appear yellow. Also, the concentration of neutral shallow donors, as monitored by electron paramagnetic resonance (EPR), is significantly reduced. A photoinduced EPR signal due to neutral nitrogen acceptors is observed when the ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(123 citation statements)
references
References 20 publications
12
110
1
Order By: Relevance
“…12,42 This trend indicates that with low nitrogen doping the electron has an effective role which corresponds to n-type conductivity. However, the inverse conductivity type is observed with higher order of N-doping which is in relation to previous reports, 19,43 The Fermi level stretched towards valence band maxima in this situation as nitrogen supposed to be the acceptor impurity in ZnO, [44][45][46] therefore, it enhances more hole in valence band instead of electrons in conduction band which leads shift of Fermi level near to the valence band maxima to compensate the Law of Mass Action. 47 The relationship of BursteinMoss shift with optical band gap and the conductivity type of material is found quite interesting …”
Section: Aip Advances 8 035212 (2018)mentioning
confidence: 39%
“…12,42 This trend indicates that with low nitrogen doping the electron has an effective role which corresponds to n-type conductivity. However, the inverse conductivity type is observed with higher order of N-doping which is in relation to previous reports, 19,43 The Fermi level stretched towards valence band maxima in this situation as nitrogen supposed to be the acceptor impurity in ZnO, [44][45][46] therefore, it enhances more hole in valence band instead of electrons in conduction band which leads shift of Fermi level near to the valence band maxima to compensate the Law of Mass Action. 47 The relationship of BursteinMoss shift with optical band gap and the conductivity type of material is found quite interesting …”
Section: Aip Advances 8 035212 (2018)mentioning
confidence: 39%
“…This signal was also assigned to shallow donors and its position appears to be independent on the shallow donor intensity. 26 Recently, Djurisic et al 12,27 found that there is no simple relationship between the intensity of g ϳ 1.96 EPR signal and the visible PL; the green PL is observed for the samples which do not show EPR line at g ϳ 1.96, and they conclude that the most likely explanation for the green luminescence involves multiple defects and/or defect complexes and the major part of the visible emission originates from the centers at the nanostructures surface. Xu et al 28 calculated the levels of various defects including complex defects V O :Zn i and V Zn :Zn i .…”
Section: -4mentioning
confidence: 99%
“…Indeed isolated nitrogen acceptors (N O ) were identified by electron paramagnetic resonance (EPR) spectroscopy. [1][2][3] The EPR signals of the isolated nitrogen centers were first observed in nominally undoped ZnO single crystals and later also in ammonia treated ZnO powders. 4,5 To our knowledge, the isolated nitrogen acceptors were never observed in intentionally doped epitaxial films or single crystals, although evidence for the presence of high concentrations of nitrogen was obtained by other characterization methods.…”
Section: Introductionmentioning
confidence: 99%